Efficacy of IVUS-guided stent implantation in patients with complex CAD: a meta-analysis based on RCTs - Xu, Anyi; Wang, Dongying; Chen, Bangsheng; Song, Siyue; Zhang, Qiufeng; Zhu, Zuokun; Dai, Min; Wang, Chenyi (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThis study is to investigate the efficacy of stent implantation in patients with complex coronary artery disease (CAD) under intravascular ultrasound (IVUS) guidance and non-IVUS guidance.MethodsWe conducted a systematic search in PubMed, Web of Science, Cochran, and Embase for the articles of IVUS-guided and non-IVUS-guided stent implantation in patients with complex CAD and reported related outcomes. We included major adverse cardiovascular events (MACE), myocardial infarction (MI), cardiac death and other outcome indicators. Relative ratio (RR) and 95% confidence interval (CI) were used for statistical analysis.ResultsA total of 5,173 subjects were included in 6 randomized control trials. The results showed that the incidence of MACE (RR: 0.63, 95% CI: 0.49–0.82, P < 0.001), cardiac death (RR: 0.61, 95% CI: 0.44–0.85, P = 0.004), target vessel revascularization (TVR) (P = 0.01), target lesion revascularization (TLR) (P = 0.03) and stent thrombosis (ST) (P = 0.002) in the experimental group (IVUS-guidance) was lower than that in the control group (non-IVUS-guidance). However, no statistical difference was observed between the both groups in the incidence of MI (P = 0.13) and all-cause death (P = 0.41).ConclusionsCompared with the non-IVUS-guided group, IVUS-guided stent implantation may be more effective for patients with complex CAD.Systematic Review RegistrationPROSPERO [CRD42024531366].